Transgenic 6F tomatoes act on the small intestine to prevent systemic inflammation and dyslipidemia caused by Western diet and intestinally derived lysophosphatidic acid[S] - Mohamad Navab; Greg Hough; Georgette M. Buga; Feng Su; Alan C. Wagner; David Meriwether; Arnab Chattopadhyay; Feng Gao; Victor Grijalva; Janet S. Danciger; Brian J. Van Lenten; Elin Org; et al. (Journal of Lipid Research, 2013)
We recently reported that levels of unsaturated lysophosphatidic acid (LPA) in the small intestine significantly correlated with the extent of aortic atherosclerosis in LDL receptor-null (LDLR−/−) mice fed a Western diet (WD). Here we demonstrate that WD increases unsaturated (but not saturated) LPA levels in the small intestine of LDLR−/− mice and causes changes in small intestine gene expression. Confirmation of microarray analysis by quantitative RT-PCR showed that adding transgenic tomatoes expressing the apoA-I mimetic peptide 6F (Tg6F) to WD prevented many WD-mediated small intestine changes in gene expression. If instead of feeding WD, unsaturated LPA was added to chow and fed to the mice: i) levels of LPA in the small intestine were similar to those induced by feeding WD; ii) gene expression changes in the small intestine mimicked WD-mediated changes; and iii) changes in plasma serum amyloid A, total cholesterol, triglycerides, HDL-cholesterol levels, and the fast-performance liquid chromatography lipoprotein profile mimicked WD-mediated changes. Adding Tg6F (but not control tomatoes) to LPA-supplemented chow prevented the LPA-induced changes. We conclude that: i) WD-mediated systemic inflammation and dyslipidemia may be in part due to WD-induced increases in small intestine LPA levels; and ii) Tg6F reduces WD-mediated systemic inflammation and dyslipidemia by preventing WD-induced increases in LPA levels in the small intestine.